The Relevance and Potential Role of Orbital Fat in Inflammatory Orbital Diseases: Implications for Diagnosis and Treatment - Prince Dadson; Peter Ngum; Luis Eduardo Juarez-Orozco; Michael Ntodie; Piotr Loba (Ophthalmology and Therapy)
Abstract The orbit is an important structure within the skull that houses the eye, optic nerve, and extraocular muscles. It also contains adipose/fat tissue, which provides a protective cushion for these components. Inflammatory orbital disease can affect any or all components of the orbit, often arising from various underlying pathologic conditions, including autoimmune, infectious, and vascular diseases. Typical signs and symptoms of orbital inflammation include swelling, redness, pain, discomfort, and potential loss of function. The role of orbital fat in the pathogenesis of inflammatory orbital diseases has not been fully explored. This review aims to provide a comprehensive description of orbital fat, its relevance and the potential role in inflammatory diseases of the orbit, and the use of radiologic imaging studies for evaluating this fat depot in cases of as inflammatory orbital diseases. Additionally, this review discusses the various procedures available for the treatment and management of these conditions. A range of interventions, including pharmacotherapy and surgical procedures, will be evaluated as promising therapeutic options. This review also explores the characteristics and potential applications of orbital fat-derived stem cells, with an emphasis on their regenerative abilities and anti-inflammatory effects. Understanding the role of orbital fat and its contribution to inflammatory orbital diseases is essential for optimizing diagnostic and treatment strategies.